Immunohistochemical localisation of vitamin B12 R-binder in the human digestive tract. Issue 3 (March 1987) - Kudo, H; Inada, M; Ohshio, G; Wakatsuki, Y; Ogawa, K; Hamashima, Y; Miyake, T
Abstract : The distribution of vitamin B12 R-binder in the human digestive tract was studied using an indirect immunoperoxidase technique. Positive staining for R-binder was found in the mucous cells and ductal epithelial cells of the salivary glands and the oesophageal glands. In normal gastric mucosa, no positive staining for R-binder was found, but in the area with intestinal metaplasia, the columnar epithelial cells and goblet cells showed positive staining. Epithelial cells of the gallbladder, intrahepatic bile ducts and pancreatic ducts were also positive for R-binder. In the small intestine and colon, R-binder was found in the columnar epithelial cells and goblet cells. The measurement of unsaturated vitamin B12 binding capacity and cobalamin content in the extracts from intestinal mucosa also indicated the presence of R-binder in the intestinal mucosa.